Modified Picture Series through Hot Potatoes in Increasing Students’ Reading Comprehension - Syamsiah Depalina Siregar (Institut Agama Islam Negeri (IAIN) Padangsidimpuan, 2020)
This article describes pictures series modified using digital text through Hot Potatoes. Classroom action research is used to discover the process of improving text reading comprehension by modifying serial images using digital text. The classroom action research used consisted of two cycles. The instrument used in this study was a written test in the form of an essay using the hot potatoes application, observation sheets and questionnaires with the help of Google forms and conversations with the help of voice messages on the WhatsApp application. The findings in this article are that in the new normal era, students are faced with new habits of learning with the help of the internet with various applications. Therefore, there is a new climate that emerges in the learning process itself, from refusing to be comfortable with online learning habits. Educators must be more creative in creating learning activities in this network, so as to improve students' learning abilities, especially reading skills.